Behavioural Response Alteration in Caenorhabditis elegans to Urine After Surgical Removal of Cancer: Nematode-NOSE (N-NOSE) for Postoperative Evaluation. Issue 11 (December 2019) - Kusumoto, Hirotake; Tashiro, Kotaro; Shimaoka, Syunji; Tsukasa, Koichiro; Baba, Yukiko; Furukawa, Saori; Furukawa, Junichiro; Suenaga, Toyokuni; Kitazono, Masaki; Tanaka, Sadao; Niihara, Toru; Hirotsu, Takaaki; et al.
The technique used for cancer monitoring is essential for effective cancer therapy. Currently, several methods such as diagnostic imaging and biochemical markers have been used for cancer monitoring, but these are invasive and show low sensitivity. A previous study reported that Caenorhabditis elegans sensitively discriminated patients with cancer from healthy subjects, based on the smell of a urine sample. However, whether C. elegans olfaction can detect the removal of cancerous tumours remains unknown. This study was conducted to examine C. elegans olfactory behaviour to urine samples collected from 78 patients before and after surgery. The diagnostic ability of the technique termed Nematode-NOSE (N-NOSE) was evaluated by receiver operating characteristic (ROC) analysis. The ROC curve of N-NOSE was higher than those of classic tumour markers. Furthermore, we examined the change in C. elegans olfactory behaviour following exposure to preoperative and postoperative samples. The results suggest that a reduction in attraction indicates the removal of the cancerous tumour. This study may lead to the development of a noninvasive and highly sensitive tool for evaluating postoperative cancer patients.